Primary Breast Mucormycosis, A Case Report - Baezzat, S R (Kowsar, 2011)
Mucormycosis is a rare fungal infection caused by organisms of the order Mucorales often occurring in diabetics or immunologically compromised patients. To date, only one case of primary mucormycosis of breast has been reported in the English literature. We describe a further case of mucormycosis that was localized to the breast in a patient with no underlying disease and was successfully treated with a simple mastectomy and intravenous antifungal therapy.